Evaluation of Polymorphism of Leu/Val of Growth Hormone Gene in Friesian Holstein Cows at Breeding Centre of Dairy Cattle Baturraden - Mu’in, MA; Zurahmah, N (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
The Leu/Val polymorphism of the growth hormone evaluation was studied in 35 Friesian Holstein dairy cow at Baturraden Breeding Centre of Dairy Cattle. A 211 bp DNA fragment of GH gene spanning from the forth intron region (49 bp) to fifth of exon (162 bp) was amplified and digested with AluI restriction enzyme to identified polymorphism at this locus. Allele frequencies of variant Leu (leucine) and Val (valine) were 0.91 and 0.09, respectively. Selection to raising of Val allele frequencies have probably to increase of milk production at population of Friesian Holstein dairy cow at Baturraden Breeding Centre of Dairy Cattle. (Animal Production 11(3): 155-159 (2009)Â Key Words: gene, growth hormone, Leu/Val polymorphism, Friesian Holstein